Concepção de produção de texto na escola: os reflexos no ensino da língua materna na sala do 5º ano do Ensino Fundamental - Ferreira, Simônica da Costa [UNESP] (2015)
This study presents a research developed at the Graduate Program - Master - the Faculty of Science and Technology FCT / Unesp in the town of Presidente Prudente and is linked to the line Childhood and Education, and analyzes the concept of production of texts teachers of the 5th year of elementary school at a school located in Alvares Machado - SP. In the educational field, the prospects related to reflection in regard to dialogicity in producing student texts have led many researchers to reflect on the role of teacher in the classroom, as the educator the mediator of the educational process. To this end, it is worth mentioning the importance of designing dialogic language in the teaching-learning process that is linked to the mother tongue. Thus, we investigated what the design of production of four teachers of the 5th year of elementary school texts in order to investigate the design of textual production, working methodology and written text evaluation. Because in addition to having several researches related to the subject, held in the past, this theme continues in vogue. Thus, this research work is part of the field of qualitative research in education. The interviews took place in four individual meetings, of which the conversation was particularly held with each teacher on different days. For the analyzes, we rely on the authors Bakhtin (2011); Geraldi (2011); Koch and Elias (2014); Menegassi (2008) among others, which gave us support so we could discuss matters that have been made in the interview...